2014
DOI: 10.1002/nur.21604
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Compromised Parenting in Low-Income Mothers of Infants and Toddlers: Distal and Proximal Risks

Abstract: Low-income mothers develop depressive symptoms at higher rates than the general population, adding to the existing risk that economic hardship places on their infants and toddlers. Emphasizing a few key intervention targets, an approach that is especially relevant to mothers when depressive symptoms compromise their energy and concentration, can improve interventions with populations facing adversity. The goal of this study was to identify contextual risk factors that significantly contributed to depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 67 publications
(80 reference statements)
4
24
1
Order By: Relevance
“…This is a secondary analysis of combined data from two randomized clinical trials (RCTs) conducted from 2003–2010 in low-income communities in North Carolina and New York [ 28 30 ]. The RCTs were focused on decreasing maternal depression symptoms through an interpersonal psychotherapy/parent enhancement intervention, and the control group received either usual care or an equal attention, health education condition; both groups received parenting guidance and wrap around services as part of federal Early Head Start programming; further details about the parent RCT designs and findings can be found elsewhere [ 28 30 ]. In the parent RCTs the total sum-score of the Center for Epidemiological Studies Depression scale (CES-D) was used as a measure of change in depression severity.…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary analysis of combined data from two randomized clinical trials (RCTs) conducted from 2003–2010 in low-income communities in North Carolina and New York [ 28 30 ]. The RCTs were focused on decreasing maternal depression symptoms through an interpersonal psychotherapy/parent enhancement intervention, and the control group received either usual care or an equal attention, health education condition; both groups received parenting guidance and wrap around services as part of federal Early Head Start programming; further details about the parent RCT designs and findings can be found elsewhere [ 28 30 ]. In the parent RCTs the total sum-score of the Center for Epidemiological Studies Depression scale (CES-D) was used as a measure of change in depression severity.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers’ interactions with their spouses or partners may serve as a model for interacting with and forming a positive, warm, supportive relationship with their children. Beeber et al () reported that being married or having a live‐in partner was linked to mothers’ providing developmental stimulation and more effective parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Within this group, 1.5 million families live in extreme or deep poverty, a category alternately defined as living on $2.00 or less per day, per family member (Ekono, Jiang, & Smith, 2016; Quiggin & Mahadevan, 2010; Sachs, 2007), at 50% below the federal poverty level (Beeber et al, 2014), or in a neighborhood where 40% or more of residents live below the federal poverty level (Ludwig et al, 2012). …”
Section: Introductionmentioning
confidence: 99%